1995
DOI: 10.1111/j.1365-2958.1995.18050867.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori picB, a homologue of the Bordetella pertussis toxin secretion protein, is required for induction of IL‐8 in gastric epithelial cells

Abstract: Approximately 60% of Helicobacter pylori strains are cagA+ and this genotype is more frequently associated with duodenal ulcer disease. Although most wild-type cagA+ strains are both cytotoxigenic and induce enhanced Interleukin-8 (IL-8) secretion in gastric epithelial cells, isogenic cagA- mutants retain full activity in these assays; thus, cagA appears to be a marker of enhanced virulence. Delineation of the nucleotide sequence of a 4 kb region upstream of cagA allowed the identification of 966 bp (picA) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
237
1
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(249 citation statements)
references
References 27 publications
(50 reference statements)
8
237
1
3
Order By: Relevance
“…It is clear that there are four ORFs in cagII with protein level homologies to some of the A. tumefaciens vir genes that are needed for T DNA transfer to target plant cells, and corresponding transfer genes from conjugative bacterial plasmids. Three of these four genes are homolouges of the ptl genes of B. pertussis that are needed to deliver pertussis toxin to mammalian cells [vir B11/ ptl H (ORF11), vir B10/ptlG (ORF13ؒ14) and vir B9/ptl F (ORF15)], whereas a homologue of the fourth [virD4 (ORF10)] has not been found in B. pertussis; a homologue of a fifth such vir/ptl gene also was found in the right (cagI) half of this PAI (picB, Tummuru et al, 1995; or cagE, Censini et al, 1996). The H. pylori genes for these five vir/ptl homolouges are scattered in the cag PAI, not tightly clustered as in A. tumefaciens or B. pertussis.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that there are four ORFs in cagII with protein level homologies to some of the A. tumefaciens vir genes that are needed for T DNA transfer to target plant cells, and corresponding transfer genes from conjugative bacterial plasmids. Three of these four genes are homolouges of the ptl genes of B. pertussis that are needed to deliver pertussis toxin to mammalian cells [vir B11/ ptl H (ORF11), vir B10/ptlG (ORF13ؒ14) and vir B9/ptl F (ORF15)], whereas a homologue of the fourth [virD4 (ORF10)] has not been found in B. pertussis; a homologue of a fifth such vir/ptl gene also was found in the right (cagI) half of this PAI (picB, Tummuru et al, 1995; or cagE, Censini et al, 1996). The H. pylori genes for these five vir/ptl homolouges are scattered in the cag PAI, not tightly clustered as in A. tumefaciens or B. pertussis.…”
Section: Discussionmentioning
confidence: 99%
“…The cagA gene is a marker for a large 40-kb locus containing .40 genes, termed the cag pathogenicity island (cag PAI), and the majority of these genes encode membrane-associated proteins with features similar to other bacterial secretion systems, particularly the type IV system epitomised by Bordetella pertussis toxin secretion [27][28][29]. A cagE mutant induced only mild inflammation in Mongolian gerbils, whereas the wild-type strain and vacA mutants induced more severe gastritis [30]. Mutation of cagE abolishes the ability of H. pylori to induce the cytokine interleukin-8 (IL-8), a neutrophil chemotactic factor, in Kato-3 cells [27,29,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using isogenic mutants strains lacking the cagA gene have shown that IL-8 induction may not be directly due to CagA protein but to the products of cag PAI genes. 95,105,106,107 cag PAI is a 40 kilobase segment of DNA containing over 31 genes inserted into the chromosomal glutamate racemase gene. The presence in cag PAI of the short repeated sequences similar to that found in the insertion sequence 605 (IS605), and its different proportion of G+C in comparison with the chromosomal DNA, suggests that this has been acquired by horizontal transfer.…”
Section: Relevance Of Strain Types Of H Pylori In the Outcome Of Infmentioning
confidence: 99%
“…82 In this way, the bacterial protein CagA is the virulence determinant that is actively translocated across the membrane of the gastric epithelial cells. 95,107 The gastric epithelium represents the first line of active defense against H. pylori infection. However, this tissue not only serves as barrier to exclude pathogens but also secrets a number of inflammatory mediators that initiate the host immune response to pathogen invasion.…”
Section: Relevance Of Strain Types Of H Pylori In the Outcome Of Infmentioning
confidence: 99%
See 1 more Smart Citation